2015
DOI: 10.1111/jsbm.12162
|View full text |Cite
|
Sign up to set email alerts
|

Family Business Characteristics and the Approach to HRM in Overseas Ventures

Abstract: This paper provides new evidence on the relationship between family business (FB) and human resource management (HRM) abroad. Our analysis provides two main results. First, not all organizational attributes of FBs exert the same effect on the approach to HRM abroad. Whereas participation of family members in the board of directors displays no significant impact, ownership and family managerial models favor the exploitation of the human resources supplied by the parent company. In contrast, the involvement of y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 78 publications
2
9
0
Order By: Relevance
“…We identify family control as the power to appoint to the board of directors. This definition is in line with previous studies, according to which family control can be identified as the fractional equity holding by family founding members or descendants (Bannò and Sgobbi, 2016;Lee, 2006). We define the variable that identify the nature of FBs as a binary variable equal to 1 if a non-listed firm is principally owned by the family or if no less than 20% of a listed firm is owned by the family, and zero otherwise (Littunen and Hyrsky, 2000).…”
supporting
confidence: 82%
“…We identify family control as the power to appoint to the board of directors. This definition is in line with previous studies, according to which family control can be identified as the fractional equity holding by family founding members or descendants (Bannò and Sgobbi, 2016;Lee, 2006). We define the variable that identify the nature of FBs as a binary variable equal to 1 if a non-listed firm is principally owned by the family or if no less than 20% of a listed firm is owned by the family, and zero otherwise (Littunen and Hyrsky, 2000).…”
supporting
confidence: 82%
“…Nevertheless, the usage of family managers has its limitations. Family managers may not possess the requisite experience and prior knowledge needed for EFBGs internationalization which could hence delay and restrict their progress (Bannò and Sgobbi 2016;Del Bosco and Bettinelli 2020;Vandekerkhof et al 2015). As stated previously, there are only a finite number of direct family members available useful across the FBGs.…”
Section: Family Managers As a Specific Resource Utilized During Efbgs Internationalizationmentioning
confidence: 99%
“…Emerging Market Multinational Family Business Groups and… Therefore, it is a strategic challenge for EFBGs to manage where to assign family members internationally. Conversely, most studies related to family management and family member involvement have focused on the corporate level but have ignored the pivotal role it plays during internationalization (Bannò and Sgobbi 2016;Tabor et al 2018). Our research objective is to address this gap by examining the practical utilization of family managers established in foreign subsidiaries.…”
mentioning
confidence: 99%
“…Training and development. Few works address HRD (Kotey and Folker, 2007) or its organizational outcomes (Bannò and Sgobbi, 2016;Benito-Hernández et al, 2015). For example, Loan-Clarke et al (1999) indicated that the budget for investment in managerial development practices is negatively correlated with the number of family members in the management team.…”
Section: Hr Practices In Family Businessesmentioning
confidence: 99%